2009
DOI: 10.1520/jai102128
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of RPV Materials Irradiated to High Fluences at High Flux

Abstract: Understanding the embrittlement of reactor pressure vessel (RPV) steels at high fluence region is very important for the long term operation of nuclear power plants. In this study, extensive microstructural analyses were performed on the RPV steels irradiated to very high fluences beyond 1020n/cm2, E>1 MeVat high fluxes under the Pressurized Thermal Shock and Nuclear Power Plant Integrity Management projects in Japan. Three dimensional atom probe analyses were performed to characterize the solute atom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Fukuya and coworkers [39] have reported nanostructural evolution of A533B steel with Cu contents of 0.12 and 0.16 wt.% subjected to irradiation doses from 3.1 to 6.8 Â 10 19 n cm À2 under a wide range of flux from 7.8 Â 10 10 to 5 Â 10 12 n cm À2 s À1 , the former of which is the in-service operation condition. A similar study has been made on surveillance specimens weld metals with the Cu content of 0.13 and 0.3 wt.% by Toyama et al [40] and on the various specimens irradiated in testing reactors by Soneda et al [41]. The interesting features are summarized as follows.…”
Section: Discussionmentioning
confidence: 71%
“…Fukuya and coworkers [39] have reported nanostructural evolution of A533B steel with Cu contents of 0.12 and 0.16 wt.% subjected to irradiation doses from 3.1 to 6.8 Â 10 19 n cm À2 under a wide range of flux from 7.8 Â 10 10 to 5 Â 10 12 n cm À2 s À1 , the former of which is the in-service operation condition. A similar study has been made on surveillance specimens weld metals with the Cu content of 0.13 and 0.3 wt.% by Toyama et al [40] and on the various specimens irradiated in testing reactors by Soneda et al [41]. The interesting features are summarized as follows.…”
Section: Discussionmentioning
confidence: 71%
“…An irradiation-induced grain hardening due to P was also reported for low Cu steels (Cu < 0.1%) (e.g., [53,54,55,56,57]. It has been observed that raising P content increases the number density of irradiation-induced Cu-rich defects (e.g., [55,58]), see Paragraph 8.2.…”
Section: Deleterious Impuritiesmentioning
confidence: 72%
“…Ni alone has a low impact on the formation of Cu-rich clusters [67], while Mn alone strongly increases their number density and volume fraction [133], and ii) for a given Mn content, their number density and volume fraction sharply increase with Ni [67]. The latter result has been confirmed on RPV steels (e.g., [58]). -Long term aging (up to 100,000 hours) at 330°C on high Cu steels (Cu > 0.4 wt%) leads to the formation of Cu-rich precipitates made of a Cu-rich core surrounded by a shell of Mn, Ni and Si atoms, very similar to clusters obtained after neutron irradiation [134,135].…”
Section: Hardening Defectsmentioning
confidence: 91%
See 2 more Smart Citations